Distribution of ABO and Rh blood grups in candidates to donors from el Tocuyo. Venezuela. (Revista Venezolana de Salud Pública, 2019)
Characterize the venezuelan population through blood groups is important by the susceptibility that each individual has to suffer accidents or be the victim of a violent act. Therefore, the objective of the study was to determine the frequency of the ABO and Rh blood systems of the candidates to donors who went to Dr. Egidio Montesinos Hospital in the city El Tocuyo in Lara state, during the period 2010 to 2018, For this purpose, 9251 blood samples were studied by the tube hemagglutination technique with monospecific sera, based on an antigen-antibody reaction in which agglutinogens and agglutinins of the ABO and Rh systems are investigated. The frequency of expression of these systems was determined and stratified by the variables described. Thus, 57% of the population was classified as group O for this period and group AB was the least frequent group with 2%. The Rh system showed that the positive phenotype is preponderant, demonstrated by 91% of those studied over 9% of the population with Rh negative. The municipality of Morán represented the area with the highest attendance with 76% of the total studied and the male influx was around 82%. The found frequencies of blood groups in this study are similar to those observed in other investigations and other countries where miscegenation in population exists.
Keywords: blood groups; antigens; antigen-antibody reactions